(C4C1Im)6[Hg7Se10]: The Salt of a Molecular Selenido Mercurate Anion Obtained from Ionic Liquids. Issue 22 (2nd August 2018) - Donsbach, Carsten; Dehnen, Stefanie
Abstract : A binary selenido mercurate anion exhibiting a novel metalate topology was obtained as its salt (C4 C1 Im)6 [Hg7 Se10 ] (1 ) upon treatment of the ternary selenido mercurate K2 [Hg2 Se3 ] in the ionic liquid (C4 C1 Im)[BF4 ] (C4 C1 Im = 1‐butyl‐3‐methylimidazolium) in the presence of small amounts of 1, 2‐diaminoethane (en) at slightly elevated temperatures (80 °C). The three‐dimensionally extended anionic substructure was disassembled this way with formation of the unprecedented heptanuclear anion [Hg7 Se10 ] 6– . The light yellow crystals of1 are extremely sensitive to air and moisture. The structure of1 was determined by single‐crystal X‐ray diffraction, and its heavy element composition was analyzed and confirmed by micro X‐ray fluorescence spectroscopy (μ‐XFS). Abstract :